2017
DOI: 10.1192/bjp.bp.117.198952
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stage, comorbidities and treatment on survival among cancer patients with or without mental illness

Abstract: Earlier research suggests poorer outcome of cancer care among people with severe mental illness (SMI).To assess the effect of stage at presentation, comorbidities and treatment on differences in survival among cancer patients with and without a history of SMI in Finland.The total population with a first cancer diagnosis in 1990-2013 was drawn from the Finnish Cancer Registry. Hospital admissions because of SMI and deaths were obtained from administrative registers. We calculated Kaplan-Meier estimates and Cox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 28 publications
0
17
0
5
Order By: Relevance
“…As the rate and risk of suicidal deaths have decreased, the focus could be partly adjusted into those causes of death which are increasing, namely cardiovascular causes and cancer. A recent study found that persons with history of psychotic disorders had a higher mortality due to cancer, although cancer stage and comorbidity did not explain the mortality differences, which were increasing over time . In addition, the mean age at death for persons with schizophrenia is approximately at a level which the general population exhibited 30 years in the past, i.e., in 2014, their mean age at death was close to the general population's death age in the mid‐1980s.…”
Section: Discussionmentioning
confidence: 95%
“…As the rate and risk of suicidal deaths have decreased, the focus could be partly adjusted into those causes of death which are increasing, namely cardiovascular causes and cancer. A recent study found that persons with history of psychotic disorders had a higher mortality due to cancer, although cancer stage and comorbidity did not explain the mortality differences, which were increasing over time . In addition, the mean age at death for persons with schizophrenia is approximately at a level which the general population exhibited 30 years in the past, i.e., in 2014, their mean age at death was close to the general population's death age in the mid‐1980s.…”
Section: Discussionmentioning
confidence: 95%
“…The goal of such efforts is not complete abstinence, but exerting enough control over illicit drug and alcohol use to allow palliative care interventions to decrease suffering [59]. The presence of substance use disorder and psychosis in cancer is also a potential contributory factor for excess mortality in people with cancer [60].…”
Section: Discussionmentioning
confidence: 99%
“…I tillegg til at pasienter med ruslidelse og/eller psykisk lidelse ofte har flere risikofaktorer for kreft, kan både forhold ved pasienten og helsevesenet påvirke diagnostisering og behandling av kreft (15).…”
Section: «Opptil 84 Prosent Av Personer I Rusbehandling Røyker»unclassified
“…En forklaring er at den økte kreftdødeligheten reflekterer ulikheter i behandlingskvalitet (5,15,16). Pasienters bekymringer rundt somatisk helse tas ikke alltid alvorlig av leger og helsepersonell, fordi symptomer tillegges den psykiske lidelsen (1, 4, 16, 17).…”
Section: «Opptil 84 Prosent Av Personer I Rusbehandling Røyker»unclassified